2018
DOI: 10.7759/cureus.2429
|View full text |Cite
|
Sign up to set email alerts
|

Re-salvage MRI-guided Focal High-dose-rate Brachytherapy for Locally Recurrent Prostate Cancer

Abstract: Prostate cancer recurrences are common, even with twenty-first-century primary prostate cancer treatment modalities. The most common salvage treatment is (delayed) hormonal therapy, which is often associated with serious side-effects. Due to the risk of significant toxicity, whole-gland targeted salvage treatments remain unpopular. Consequently, developments in focal therapies have arisen. Magnetic resonance imaging (MRI)-guided focal salvage high-dose-rate brachytherapy (HDR-BT) is a novel treatment aiming fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…Irreversible electroporation and high-dose rate focal brachytherapy have also been described in a salvage context and do seem feasible after FT failure. However, evidence is scarce and warrants further assessment [22,23].…”
Section: Salvage Re-ablationmentioning
confidence: 99%
“…Irreversible electroporation and high-dose rate focal brachytherapy have also been described in a salvage context and do seem feasible after FT failure. However, evidence is scarce and warrants further assessment [22,23].…”
Section: Salvage Re-ablationmentioning
confidence: 99%
“…Although some studies on salvage brachytherapy for LR after radical radiotherapy have been reported, 3 only a few have reported on re-salvage brachytherapy for LR after salvage brachytherapy. 5,6 Maenhout et al 5 reported four cases who underwent re-salvage focal HDR brachytherapy after salvage fLDR brachytherapy, resulting in two of the four cases experiencing no BCR. Moreover, Son et al 6 reported a case who received re-salvage focal HDR brachytherapy for a LR after salvage focal HDR brachytherapy; at the 6-month follow-up, the patient had no BCR and no severe GU/GI toxicities.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 Maenhout et al 5 reported four cases who underwent re-salvage focal HDR brachytherapy after salvage fLDR brachytherapy, resulting in two of the four cases experiencing no BCR. Moreover, Son et al 6 reported a case who received re-salvage focal HDR brachytherapy for a LR after salvage focal HDR brachytherapy; at the 6-month follow-up, the patient had no BCR and no severe GU/GI toxicities. Thus, re-salvage focal brachytherapy after salvage brachytherapy has acceptable oncological outcomes, suggesting that it has potential as a treatment strategy.…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, many patients with biochemical recurrence are still treated with (deferred) ADT. 76 However, ADT is a systemic treatment and is associated with significant side effects, such as hot flushes, osteoporosis, loss of libido, erectile dysfunction, and therefore deterioration of quality of life. 77 Moreover, tumour progression under hormonal treatment (i.e.…”
Section: Locally Recurrent Prostate Cancermentioning
confidence: 99%
“…74 This opens up possibilities for re-salvage treatment. 74,76 Watchful waiting can also be a 'treatment' strategy, as in some patients the PSA only tends to increase slowly over time without immediate signs of metastatic disease. In these patients, initiation of systemic treatment can be postponed, withholding them from the toxic systemic effects.…”
Section: Focal Salvage Mri-guided High-dose-rate Brachytherapymentioning
confidence: 99%